Communication Strategy of Peace-Generation to Ward Off Identity Politics - Faiz Miftahul Huda; Mevy Eka Nurhalizah (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This research aims to describe how the Peace Generation Communication Strategy counters identity politics, which is one of the primary causes of social conflict in Indonesia. Employing a qualitative method with a phenomenological approach, this research analyzes data using the Harold D. Lasswell communication model, encompassing the components of communicator, message, channel, audience, and effect. The findings reveal that Peace Generation addresses the issue of identity politics through the Board Game for Peace scholarship program, designed to foster empathy and appreciation for diversity among youth. The The Rampung board game, created by Peacegen, simulates the reality of life in a village with diverse inhabitants, promoting collaboration, tolerance, and understanding. By tailoring its communication strategies to the needs and mindsets of younger audiences, Peace Generation effectively utilizes interactive and creative media to deliver messages of peace. This program not only encourages a shift in perspectives but also contributes to reducing the impact of identity politics in multicultural societies, fostering harmony and peaceful coexistence.